Alginate-wrapped NiO-ZnO nanocomposites-based catalysts for water treatment - Mohamed Adam Adam Abakar; Sher Bahadar Khan (Journal of Experimental Nanoscience)
Nickel oxide-zinc oxide (NiO-ZnO) nano-catalyst was embedded in a carbohydrate polymer (Alg/NiO-ZnO) was successfully synthesized and used for the (photo)catalytic conversion of deleterious contaminants such as organic dyes (Acridine Orange ‘ArO’, Methylene Blue ‘MB’, Methyl Orange ‘MO’) and 4-Nitrophenol ‘4-NP’ as well. Solar light helped photo-degradation and NaBH4-assisted reduction of organic dyes, as water pollutants, were studied using Alg/NiO-ZnO. Furthermore, utilizing Na alg/NiO-ZnO as a catalyst for the photocatalytic degradation was found to be more efficient for ArO, however catalytic reduction of MB was the best among all contaminants. Scanning electron microscopy (SEM), energy dispersive spectrometry (EDS), X-Ray Diffractometry (XRD) and Fourier Transform Infrared Spectroscopy (FTIR) techniques were used to identify the shape and structure of Alg/NiO-ZnO. To gather the data, an ultraviolet-visible (UV) spectrophotometer is employed. Data collection and processing, graph creation, and analysis were all accomplished with Origin 2018. In just 13  minutes, the reduction percentage of MB was determined to be 95.25%, while ArO underwent photocatalytic degradation up to 77.5% in 150  minutes. Several factors are used to optimize the catalytic property of Alg/NiO-ZnO in the reduction of organic dyes. Alg/NiO-ZnO thus provides a promising technique for the efficient oxidation and reduction of pollutants from industrial effluents.